Integrasi Budaya dalam Pembelajaran Kimia Hijau: Pengaruh E-Modul Berbasis Culturally Responsive Teaching terhadap HOTS - Hidayati, Ririn Eva (Inovasi: Jurnal Diklat Keagamaan, 2025)
This study focuses on developing a green chemistry e-module based on Culturally Responsive Teaching (CRT), designed to improve high-order thinking skills (HOTS) of class X students of MAN 1 Malang City. The development of the e-module follows the 4D model (Define, Design, Develop, Disseminate), involving expert validation and trials on students. The research instruments include HOTS tests, observations, interviews, questionnaires, and documentation. The validation results show that this e-module is classified as "very valid" with an average score on the aspects of language (83), presentation (84), content (84), and conformity to CRT (85). The effectiveness test results showed a significant increase in high-order thinking skills in the experimental group compared to the control group, with an n-gain value of 0.51 (moderate category) for the experimental group and 0.29 (low category) for the control group. The results of this study show that the CRT-based green chemistry e-module effectively improves students' HOTS and is relevant to local culture-based learning needs.